Identifying Factors Associated with the Development of Tamoxifen Resistance in Breast Cancer - Ojo, Diane (My University, 2017)
Breast cancer (BC) is the most common female malignancy. It is estimated that an average of 72 Canadian women will be diagnosed with BC each day. Although significant advances in BC screening and treatment has resulted in a steady decline in mortality rates, BC remains the second most common cause of cancer related deaths in women. Tamoxifen (TAM) is the most widely used treatment among women with estrogen receptor (ER) positive (ER+) BC, the major type of BC consisting of approximately 70% of cases. Although approximately 50% of patients with advanced ER+ BC initially respond to treatment, approximately 1/3 of patients treated with TAM develop resistance and recurrence. TAM resistance is thus a major challenge in BC treatment, largely owing to our limited understanding of the underlying mechanisms. In our effort to investigate these mechanisms, we have examined a number of candidates for their contributions to BC progression and the development of TAM resistance. Sharpin is a newly emerged oncogenic protein. It associates with the PTEN tumor suppressor and inactivates PTEN-derived phosphatidylinositol (3,4,5)-trisphosphate (PIP3) phosphate activity. Sharpin is also a component of the linear ubiquitin chain assembly complex (LUBAC) which plays a key role in NFB activation. In accordance with this knowledge, we have constructed three Sharpin gene amplification-derived signatures using the Metabric dataset (n=2059) within the cBioPortal database. These signatures are significantly associated with declines in overall survival (OS) in BC patients and are independent risk factors of BC death after adjusting for known clinical factors. Additionally, we demonstrated that Sharpin sustains ER+ BC cells survival of TAM-derived cytotoxicity, which is in part through activation of AKT and NFB signaling. The development of TAM resistance is a complex process, and is regulated by complex mechanisms or factors. Indeed, my research also revealed BMI1 being important in conferring resistance to TAM in ER+ BC. BMI1 is a well-known oncogenic protein in various human cancers; it demonstrates oncogenic functions in part through sustaining cancer stem cells and repression of tumor suppressors, p16INK4A and p14ARF. While evidence reveals BMI1 promoting breast cancer stem cells, whether BMI1 promotes resistance to TAM remains unknown. By using comprehensive approaches, we demonstrated that BMI1 confers ER+ BC cell resistance to TAM in vitro and in vivo. In patients, BMI1 expression is associated with ER+ BC, and contributes to resistance to endocrine therapy. Furthermore, BMI1 promotes TAM resistance in part through upregulation of pathways and factors that play important roles in TAM resistance, including ER signaling, MUC1, and androgen receptor (AR). AR contributes to TAM resistance through conversion of TAM from an ER antagonist to an agonist. Likewise, in BMI1 overexpressing MCF7 cell-derived xenograft tumors, TAM stimulates tumor growth, suggesting BMI1 enhancing the agonist activity of TAM. Besides Sharpin and BMI1-derived oncogenic functions, our research suggests CYB5D2 providing tumor suppressor function towards BC and the development of TAM resistance. CYB5D2 was originally identified for its role in promoting neurogenesis. Recently, it has also been acknowledged as a tumor suppressor in cervical cancer. We demonstrate CYB5D2 downregulation in primary breast tissues and following the development of TAM resistance in vitro and in vivo. Furthermore, downregulation of CYB5D2 is significantly associated with a reduction in OS in patients with BC. Taken together, this thesis demonstrates three novel factors, including both oncogenic and a potential tumor suppressing factors, which contribute to TAM resistance. These findings improve on our knowledge of BC progression as well as the development of TAM resistance in ER+ BC. The knowledge uncovered here will have applications in improving management for patients with BC.